Investigating Problem Solving Skills and Chemistry Learning Experiences of Higher Education Base on Gender and Grade Level Differences - Dwi Wahyudiati (Journal of Science and Science Education, 2021)
The purpose of this study was to investigate the problem-solving skills (PSS) and chemistry learning experiences (LE) of teacher candidates. 191 pre-service chemistry teacher (130 women, 61 men) were taken as the research sample using the purposive random sampling technique. The research design used a cross-sectional survey with focus group interviews. The quantitative data obtained were analyzed using the MANOVA test and while the interview data using the Patton analysis technique. The research findings show that: 1) the level of the chemistry learning experience of pre-service chemistry teacher (LE) is higher than the ability of problem-solving skills (PSS); 2) the level of ability of female chemistry teacher candidates for PSS and LE was found to be higher than that of males; (3) there are differences in PSS and LE based on grades levels, but there is no difference based on gender; 4) there is a difference in PSS and LE between freshman, sophomore, and junior grades. The findings of the interview are relevant to the results of the survey which proved that male and female students both have positive attitudes towards chemistry, however, it was found that there were differences in PSS and LE between grade level (1stgrade, 2stgrade, 3st grade). Thus, it is suggested that the learning process in universities prioritizes the development of LE and PSS in chemistry learning so as to improve the soft skills and academic achievement of prospective chemistry teachers.